The cardiorespiratory system state of the 10th -11th grade boys after the introduction of the variable module "CrossFit" - Anhelina Petrova; Tetiana Bala (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the cardiorespiratory system state of the 10th-11th grade boys after the introduction of CrossFit exercises. Material and methods: theoretical analysis and generalization of scientific methodological literature; biomedical methods for determining the physical health of pupils (spirometry, tonometry, pulsometer, Stange's test); pedagogical experiment and methods of athematical statistics. The cardiorespiratory system state was determined by indicators of the regulation level of the cardiovascular system (Robinson's index) and the functional capabilities of the respiratory system, and the body's resistance to hypoxic phenomena (Skibinski's index). Resting heart rate (bpm-1), systolic blood pressure (mmHg), lung capacity (ml), breath retention time at inhalation (Stange'stes t) (s) were determined to calculate indicators. The obtained indicators were calculated for the formulas: HR (bpm-1) × BP Syst. (mmHg )/100 (Robinson's index); LC (ml) × Stange's test (s )/HR (bpm-1) (Skibinski's index). The examined results were compared to the scale and evaluated with a certain number of scores. Statistical analysis: the research materials were processed using the licensed Excel program. In the research 52 pupils of the 10th -11th grades took part. Results: it was established that the cardiorespiratory system state improved after the introduction of CrossFit exercises into the educational process on physical education of the 10th -11th grade boys. Conclusions: the positive effect of CrossFit exercises on the state of cardiorespiratory system of 10th-11th grade boys of main groups was found.